FLIPPED CLASSROOM APPLIED IN ENGLISH LANGUAGE TEACHING - Dwi Nugroho, Andhi (Universitas Wiralodra, 2021)
The paper explored the flipped classroom model applied in English Language Teaching including its applications, components, benefits, and challenges likely to be experienced in the application process of the model. The data were national and international journal articles reporting flipped classroom model. The study applied content analysis to investigate the area of studies, online platforms or technology tools, and impacts on students learning. The results of the analysis were interpreted using descriptive analysis. It was found that the flipped classroom model was in various teaching fields, and some technology tools were used as the online platforms for teaching practices. The analysis of the impacts of flipped classroom models covered students’ learning achievement, engagement, and interaction. The challenges in the application of flipped classroom model were expected to be taken into consideration by future researchers. To sum up, the study provided implications for education stakeholders or policymakers to determine the application of flipped classroom model in the future.